DILEMA SISTEM MULTIPARTAI DALAM SISTEM PRESIDENSIAL DI INDONESIA - Dina Fadiyah (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2022)
There are several kinds of governance systems in the world such as the presidential and parliamentary. Each system has advantages and disadvantages of government, characteristics, and individual differences. But it also has a system of government which makes it a perfect indicator, while Indonesia adheres to a presidential system and a multiparty system as well. The problem is when these two systems can not run well because the two systems should not constitute a suitable system.